Pengembangan Literasi Al-Quran Untuk Penguatan Karakter Perguruan Tinggi Islam - Ruswan Ruswan; Nadhifah Nadhifah; Camila Fatah Suroyya (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2025)
Islamic higher education institutions are established not merely as centers for the development of knowledge, but more importantly as institutions aimed at producing young Muslim generations who are committed to practicing Islamic teachings and values. Therefore, the Islamic character of higher education institutions must be strengthened through various strategic efforts, including curriculum development, educational facilities, and institutional reinforcement. This article examines the efforts of Universitas Islam Sultan Agung (UNISSULA) and Universitas Muhammadiyah Semarang (UNIMUS) in strengthening their Islamic character through the development of Qur’anic literacy. Research data were collected through interviews, documentation, and observations. The findings indicate that the development of Qur’anic literacy has become one of the key strategies for reinforcing the Islamic character of UNISSULA and UNIMUS. This initiative is implemented alongside other measures, such as the formulation of institutional vision, mission, and objectives that explicitly affirm the Islamic identity of both universities, as well as the establishment of specialized institutions tasked with enhancing students’ Islamic knowledge and fostering an Islamic campus culture. The findings indicate that the enhancement of Qur’anic literacy significantly contributes to the improvement of students’ reading and writing skills, comprehension, and internalization of Qur’anic values in their daily lives. Clear institutional structures, adequate resource support, and the integration of academic and religious activities are key factors in the success of these programs. These findings can serve as a reference for other Islamic higher education institutions in designing adaptive and comprehensive Qur’anic literacy programs capable of shaping consistent Islamic character across all dimensions of campus life